2015
DOI: 10.1016/j.earscirev.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton dynamics from the Cambrian Explosion to the onset of the Great Ordovician Biodiversification Event: A review of Cambrian acritarch diversity

Abstract: Most early Palaeozoic acritarchs are thought to represent a part of the marine phytoplankton and so constituted a significant element at the base of the marine trophic chain during the 'Cambrian Explosion' and the subsequent 'Great Ordovician Biodiversification Event.' Cambrian acritarch occurrences have been recorded in a great number of studies. In this paper, published data on Cambrian acritarchs are assembled in order to reconstruct taxonomic diversity trends that can be compared with the biodiversity of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 92 publications
0
30
0
Order By: Relevance
“…At a larger scale, phytoplankton diversity increased continuously from the early Cambrian to the Middle-Late Ordovician (Fig. 3), mirroring to some extent the biodiversity of marine invertebrates, at least during the Cambrian (Nowak et al 2015), and possibly also during the Ordovician (Hints et al 2010).…”
Section: The Plankton Revolutionmentioning
confidence: 95%
See 2 more Smart Citations
“…At a larger scale, phytoplankton diversity increased continuously from the early Cambrian to the Middle-Late Ordovician (Fig. 3), mirroring to some extent the biodiversity of marine invertebrates, at least during the Cambrian (Nowak et al 2015), and possibly also during the Ordovician (Hints et al 2010).…”
Section: The Plankton Revolutionmentioning
confidence: 95%
“…), mirroring to some extent the biodiversity of marine invertebrates, at least during the Cambrian (Nowak et al . ), and possibly also during the Ordovician (Hints et al . ).…”
Section: Biodiversification(s) At the Level Of Individual Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowak et al . () effectively observed a dramatic increase in diversity of the acritarchs, that is the organic‐walled fraction of the phytoplankton, in the late Cambrian – Early Ordovician interval. But do the higher diversities of phytoplanktonic organisms also indicate an increased abundance of phytoplankton and an increased biomass?…”
Section: Ordovician Biomass and The Sedimentary Recordmentioning
confidence: 99%
“…Based on Martin et al (2008), Servais et al (2016) further considered that the increasing presence of planktonic organisms in the late Cambrian -Early Ordovician must coincide with increasing nutrient supply, increased primary productivity and expanded biomass production that resulted during the initiation of the GOBE with a higher diversity and increased abundance of plankton-feeding groups during the Ordovician. Nowak et al (2015) effectively observed a dramatic increase in diversity of the acritarchs, that is the organic-walled fraction of the phytoplankton, in the late Cambrian -Early Ordovician interval. But do the higher diversities of phytoplanktonic organisms also indicate an increased abundance of phytoplankton and an increased biomass?…”
Section: Ordovician Biomass and The Sedimentary Recordmentioning
confidence: 99%